First polarisation measurement of coherently photoproduced J/ψ in ultra-peripheral Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Nath, Abhishek; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (Physics letters, 2025)
The first measurement of the polarisation of coherently photoproduced J/ψ mesons in ultra-peripheral Pb-Pb collisions, using data at sNN=5.02 TeV, is presented. The J/ψ meson is measured via its dimuon decay channel in the forward rapidity interval −4.0<y<−2.5 using the ALICE detector at the CERN LHC. An event sample corresponding to an integrated luminosity of 750 μb−1 ± 5% (syst) is analysed. Hadronic activity is highly suppressed since the interaction is mediated by a photon. The polar and azimuthal angle distributions of the decay muons are measured, and the polarisation parameters λθ, λφ, λθφ are extracted. The analysis is carried out in the helicity frame. The results are found to be consistent with a transversely polarised J/ψ. These values are compared with previous measurements by the H1 and ZEUS experiments. The polarisation parameters of coherent J/ψ photoproduction in Pb-Pb collisions are found to be consistent with the s-channel helicity conservation hypothesis.
Online verfügbar: 15. April 2025, Artikelversion: 23. April 2025
Im Titel steht der Ausdruck sNN unter dem Wurzelsymbol, NN ist dabei tiefgestellt
*ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, B. Windelband, A. Yuncu, F. Zanone, B. Zhang [und 1020 weitere Personen]
Gesehen am 02.03.2026